Wonder - Palacio, R. J.; Carpenter, Tad (New York Alfred A. Knopf, 2012)
Ten-year-old Auggie Pullman, who was born with extreme facial abnormalities and was not expected to survive, goes from being home-schooled to entering fifth grade at a private middle school in Manhattan, which entails enduring the taunting and fear of his classmates as he struggles to be seen as just another student.
Keywords: Sách tham khảo